Effects of soil spatial variability on axisymmetric versus plane strain analyses of ground improvement by prefabricated vertical drains - Bari, Wasiul; Shahin, Mohamed; Nikraz, Hamid (J Ross Publishing Inc, 2012)
Although soil consolidation around an individual drain is more appropriately analyzed as an axisymmetric problem, most previous numerical studies regarding soil consolidation via prefabricated vertical drains were conducted on the basis of plane strain conditions so as to achieve run-time efficiency. Under deterministic conditions, it was found in the literature that the matching theories give satisfactory equivalence between plane strain and axisymmetric analyses. Nevertheless, the matching theories have never been examined for the more realistic stochastic soil consolidation approaches and this study aims to investigate such an issue. In this paper, a stochastic approach using the Monte Carlo technique is utilized considering soil permeability as the most significant random field and the equivalence between the axisymmetric and plane strain analyses are examined.